Comparison of methods for certification of stannic, stibium and lead traces in reference materials for steel - I. V. Khodakovskaya; G. N. Popkova; V. V. Bazianova (Стандартные образцы)
Development and introduction of new metallurgical technologies, new additional chemical compound indexes controlled in metallurgical materials demand to develop the new, more advanced methods of analytical control. The particular attention should be paid to identify the traces of stannic, stinium and lead because of their influence on metal characteristics.